Analysis of The Role of E-Commerce in Improving Students' Entrepreneurial Interest and Activities - Sumiati Tahir; Agus Syam; Nurhayani; Hasisa Haruna; Pahrul (Global Research Collaboration, 2025)
Advances in digital technology have brought significant changes to the business world, particularly through the use of e-commerce. Ease of internet access and various digital platforms provide opportunities for young people, including students, to participate in entrepreneurial activities. This study aims to analyze the role of e-commerce on the entrepreneurial interests and activities of students in the Entrepreneurship Study Program, Faculty of Economics and Business, Makassar State University. The research method used is a literature study with a descriptive approach, namely by reviewing various scientific sources such as research journals, academic books, and scientific publications relevant to the research topic. The information obtained is then analyzed descriptively to understand the relationship between e-commerce developments and students' entrepreneurial interests and activities. The results of the study show that e-commerce developments make it easier for students to start and develop businesses because marketing, promotion, and transactions can be carried out digitally at a relatively lower cost. In addition, various previous studies have also shown that the use of digital platforms can increase entrepreneurial interest and encourage students to be directly involved in entrepreneurial activities. Therefore, e-commerce can be an effective means of supporting the development of entrepreneurship among students.